The influence of international agreements on disaster risk reduction. (15th June 2022) - Raikes, Jonathan; Smith, Timothy F.; Baldwin, Claudia; Henstra, Daniel
Abstract: Global frameworks established in 2015 – including the Sendai Framework for Disaster Risk Reduction, the 2030 Agenda for Sustainable Development, and the Paris Agreement – provide a comprehensive foundation for states to improve disaster risk management. However, the degree to which these frameworks are driving necessary changes to public policies and practices for disaster risk reduction remains questionable. This article explores the influence of these frameworks on flood and drought risk management in two federal states, Canada and Australia, and from the perspective of government practitioners. Through two Delphi studies and semi-structured interviews, the research found that although international agreements are considered valuable to the maturation of disaster risk management principles and practices, their perceived application in flood and drought risk management has been more limited. Government practitioners warn that using these frameworks to drive meaningful change to disaster risk management systems and structures risks further politicizing the field because of existing complex and deeply entrenched socio-political infrastructures. The findings highlight the fact that the ability of these global frameworks to facilitate meaningful changes toward more equitable, resilient, and sustainable disaster risk management is challenged not only by the institutional design of these agreements, but by resistant institutional structures that are embedded across levels of governance.